7, 12-Dimethylbenz(a)anthracene-Induced Myelotoxicity Differs in Mice Selected for High or Low Acute Inflammatory Response: Relationship With Aryl Hydrocarbon Receptor Polymorphism. (March 2014) - Katz, Iana Suly Santos; Albuquerque, Layra Lucy; Suppa, Alessandra Paes; de Siqueira, Débora Mathias; Rossato, Cristiano; Silva, Graziela Batista da; Jensen, José Ricardo; Starobinas, Nancy; Cabrera, Wafa Hanna Koury; De Franco, Marcelo; Borelli, Primavera; Ibañez, Olga Martinez; et al.
Polycyclic aromatic hydrocarbons, such as 7, 12-dimethylbenz(a)anthracene (DMBA), are environmental pollutants that exert multiple toxic and carcinogenic effects. Studies showed that these effects are mediated by activation of the aryl hydrocarbon receptor (AhR) and modulated by allelic variants of Ahr gene. Here, we investigated the effects of DMBA treatment in the inflammatory response and bone marrow (BM) hematopoietic function of maximal acute inflammatory response (AIRmax) and minimal acute inflammatory response (AIRmin) heterogeneous mouse lines selected for high and low acute inflammatory responsiveness, respectively. The phenotypic selection resulted in the segregation of the Ahr d and Ahr b1 alleles that confer low and high receptor ligand-binding affinity, respectively, in AIRmax and AIRmin mice. We observed a reduction in BM mature granulocyte population in AIRmin mice 24 hours after DMBA treatment while both blast and immature myeloid cells were increased. Proliferation and differentiation of BM myeloid cells in response to in vitro granulocyte-macrophage colony-stimulating factor stimulus were impaired in AIRmin-treated mice. These DMBA effects on myeloid BM cells (BMCs) affected the in vivo leukocyte migration to an inflammatory site induced by polyacrylamide beads (Biogel P-100, Bio-Rad, France) injection in AIRmin mice. On the other hand, these alterations were not observed in DMBA-treated AIRmax mice. These data indicate that DMBA affects myeloid cell differentiation and inflammatory response and Ahr b1 allele in the genetic background of AIRmin mice contributes to this effect.